Destilação fracionada em batelada do óleo essencial de cravo-da-índia : experimentos, modelagem termodinâmica e simulação - Rodrigues, Victor Hugo Silva (2020)
Essential oils are a complex mixture of terpenic hydrocarbons, present in the secondary metabolism of vegetables. The constituent compounds have bactericidal, fungicidal and antioxidant properties, indicating the obtaining of enriched fractions of essential oils in specific components. The recommended technique for this fractionation is vacuum batch fractional distillation, but the modeling and simulation of this process are poorly studied due to the reduced number of thermophysical properties of terpenes available such as pure component vapor pressure and component activity coefficients present in the liquid mixture. Due to this scenario, this work aims the theoretical-experimental study of the fractionation of clove essential oil in a batch fractionated distillation column that operates in vacuum. The vapor pressure of the major components of clove essential oil, eugenol and β-caryophyllene, was determined from the thermogravimetry (TG-DTA) results. These were applied to the modified Langmuir equation and modeled by the extended Antoine equation and the result obtained was compared with the response of CSGC-PVR predictive method. The binary parameters of the NRTL, Wilson and UNIQUAC activity coefficient models were estimated from regression of experimental liquid-vapor equilibrium data of the mixture of major compounds obtained in a Fischer Ebuliometer. In parallel, the use of the COSMO-SAC model was used to predict the activity coefficients and compared with the experimental results. The simulation of the vacuum fractional distillation process was performed using the Aspen Plus ® software, with the insertion of the properties obtained experimentally. The pure essential oil and the obtained fractions were analyzed by gas chromatography / mass spectrometry (GC/MS). The liquid-vapor equilibrium data showed the azeotropy of the mixture, making it difficult to separate the compounds by simple fractional distillation. The vapor pressure and activity coefficient models chosen presented a good representation of the experimental data and showed the need for their use instead of predictive methods.